Dynamic Ventilation and Power Output of Urban Bicyclists. Issue 1 (January 2015) - Bigazzi, Alexander Y.; Figliozzi, Miguel A.
Bicyclists' intake of air pollutants is linked to physical exertion levels, ventilation rates, and exposure concentrations. Whereas exposure concentrations have been widely studied in transportation environments, there has been relatively scant research linking on-road ventilation with travel conditions and exertion levels. This paper investigates relationships between power output, heart rate, and ventilation rate for urban bicyclists. Heart rate and ventilation rate were measured on-road and combined with power output estimates from a bicycle power model. Dynamic ventilation rates increased by 0.4% to 0.8% per watt of power output, with a mean lag of 0.8 min. The use of physiology (ventilation) monitoring straps and heart rate proxies for dynamic on-road ventilation measurements is discussed. This paper provides for a clearer and more quantitative understanding of bicyclists' ventilation and power output, which is useful for studies of pollutant inhalation risks, energy expenditure, and physical activity.